Measuring. Monitoring. Management. Control - I.N. Urvaev; S.N. Bazykin (Измерение, мониторинг, управление, контроль)
Background. The current task of modern robotics is the development and production of unmanned underwater vehicles (UUV). Modern UUVs allow for environmental and climate monitoring, oceanographic research, servicing of deep-sea systems and objects, search for underwater deposits, protection of water areas, etc. The use of UUVs allows not only to relieve a person from dangerous work, but also makes it possible to carry out a wide range of operations that are fundamentally inaccessible to a person. The aim of the work is to study the hydrodynamics of an underwater vehicle to optimize its design and units of the propulsion control system at the early stages of its design. Materials and methods. To solve the tasks set in the work, three-dimensional modeling methods were used using the SolidWorks Flow Simulation software module. Results. A method for modeling the flow of water around an unmanned underwater bionic vehicle is proposed and its hydrodynamic parameters are studied. Conclusion. The proposed modeling method allows for a detailed assessment and visualization of the nature of the interaction of the underwater vehicle with water and optimization of the choice of design characteristics of the hull and control units of the actuators, which significantly reduces the time and cost of work at the stages of comprehension, design, implementation and operation of underwater equipment.